Analisis Konseling Individu dalam Mengatasi Trauma : Analisis Film Dear Zindagi - Lingga, Musdiansyah; Sriharini, Sriharini (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
This research aims to analyze the concept of individual counseling applied in addressing trauma, using the film "Dear Zindagi" as a case study. Trauma is a profound emotional experience that can affect an individual’s psychological well-being. Individual counseling plays a crucial role in assisting individuals in overcoming and managing the traumatic impacts. Qualitative analysis methods are employed to investigate the individual counseling techniques described in the film. Additionally, the characterization of the main characters and the counselor’s role in guiding the trauma healing process are also analyzed. The research findings indicate that the film "Dear Zindagi" provides a fairly realistic portrayal of how individual counseling can help someone overcome trauma. The conclusion of this research is that the film offers valuable insights into the importance of individual counseling as a method for addressing trauma. These findings can serve as a source of inspiration for counseling and psychotherapy practitioners to develop more holistic and effective approaches in helping individuals cope with traumatic experiences in their lives.